Four artemisinin-based treatments in African pregnant women with malaria - Pekyi, Divine (Malawi Med J, 2016)
BACKGROUND: Information regarding the safety and efficacy of artemisinin combination treatments for malaria in pregnant women is limited, particularly among women who live in sub-Saharan Africa. METHODS: We conducted a multicenter, randomized, open-label trial of treatments for malaria in pregnant women in four African countries. A total of 3428 pregnant women in the second or third trimester who had falciparum malaria (at any parasite density and regardless of symptoms) were treated with artemether-lumefantrine, amodiaquine-artesunate, mefloquine-artesunate, or dihydroartemisinin-piperaquine. The primary end points were the polymerase-chain-reaction (PCR)-adjusted cure rates (i.e., cure of the original infection; new infections during follow-up were not considered to be treatment failures) at day 63 and safety outcomes. RESULTS: The PCR-adjusted cure rates in the per-protocol analysis were 94.8% in the artemether-lumefantrine group, 98.5% in the amodiaquine-artesunate group, 99.2% in the dihydroartemisinin-piperaquine group, and 96.8% in the mefloquine-artesunate group; the PCR-adjusted cure rates in the intention-to-treat analysis were 94.2%, 96.9%, 98.0%, and 95.5%, respectively. There was no significant difference among the amodiaquine-artesunate group, dihydroartemisinin-piperaquine group, and the mefloquine-artesunate group. The cure rate in the artemether-lumefantrine group was significantly lower than that in the other three groups, although the absolute difference was within the 5-percentage-point margin for equivalence. The unadjusted cure rates, used as a measure of the post-treatment prophylactic effect, were significantly lower in the artemether-lumefantrine group (52.5%) than in groups that received amodiaquine-artesunate (82.3%), dihydroartemisinin-piperaquine (86.9%), or mefloquine-artesunate (73.8%). No significant difference in the rate of serious adverse events and in birth outcomes was found among the treatment groups. Drug-related adverse events such as asthenia, poor appetite, dizziness, nausea, and vomiting occurred significantly more frequently in the mefloquine-artesunate group (50.6%) and the amodiaquine-artesunate group (48.5%) than in the dihydroartemisinin-piperaquine group (20.6%) and the artemether-lumefantrine group (11.5%) (P<0.001 for comparison among the four groups). CONCLUSIONS: Artemether-lumefantrine was associated with the fewest adverse effects and with acceptable cure rates but provided the shortest posttreatment prophylaxis, whereas dihydroartemisinin-piperaquine had the best efficacy and an acceptable safety profile. (Funded by the European and Developing Countries Clinical Trials Partnership and others; ClinicalTrials.gov number, NCT00852423.)